Copper(II) ionic species in Cu-II-exchanged K-offretite aluminosilicate and comparison with Cu-II-exchanged K-offretite gallosilicate determined by electron paramagnetic resonance and electron spin echo modulation spectroscopies - Yu, JS; Ryoo, JW; Lee, CW; Kim, SJ; Hong, SB; Kevan, L (ROYAL SOC CHEMISTRY, 1997)
The location of Cu-II and its interaction with deuteriated adsorbates in Cu-II-exchanged K-offretite aluminosilicate zeolite have been investigated by electron paramagnetic resonance (EPR) and electron spin echo modulation (ESEM) spectroscopies and compared with those in Cu-II-exchanged K-offretite gallosilicate. Basically similar Cu-II locations to those in CuK-offretite gallosilicate are observed in CuK-offretite aluminosilicate, but there are some interesting differences. It is found that in the fresh hydrated sample, Cu-II is, in the main channel, coordinated to three water molecules and three framework oxygens in a six-ring window of an epsilon-cage to form a distorted octahedral complex. Upon evacuation at increasing temperature, Cu-II ions move from the main channel through the E-cages to hexagonal prism sites. However, the water coordinated to Cu-II is more tightly bound in the aluminosilicate than in the gallosilicate. Dehydration produces two different Cu-II species in the aluminosilicate, both believed to be located in recessed sites owing to the lack of broadening of its EPR lines by oxygen, while only one Cu-II species is located in a recessed site in the gallosilicate. Adsorption of polar molecules such as water, alcohols, dimethyl sulfoxide, acetonitrile and ammonia cause changes in the EPR spectrum of the Cu-II indicating migration into cation positions in the main channels where adsorbate coordination can occur. However, non-polar ethene does not cause migration of Cu-II. Cu-II forms complexes with two molecules of methanol, ethanol and propanol, and one molecule of dimethyl sulfoxide based on ESEM data. Cu-II forms a trigonal bipyramidal complex with two ammonias in axial positions and three framework oxygens in a six-ring window of an epsilon-cage based on EPR parameters and ESEM data, which is the same for Cu-II in CuK-offretite gallosilicate.
Keywords: NUCLEAR MAGNETIC-RESONANCE; STRUCTURAL CHARACTERIZATION; TEMPERATURE-DEPENDENCE; PROPYLENE OXIDATION; Y ZEOLITES; X-ZEOLITE; SIMULATION; MIGRATION; SPECTRA; MAZZITE